The development of the flood victim-psychospiritual module: spiritual-religious strategies - Muhammad Idris Bullare @ Bahari; Adeymend Reny Japil; Lailawati Madlan @ Endalan; Mohd. Dahlan A. Malek; Jasmine Adela Mutang; Rosnah Ismail; Wan Anor Wan Sulaiman (EBSCOhost, 2019)
The investigation sought to explore the spiritual-religious coping strategies applied by post-flood victims. A total of 14 respondents in Kelantan and Sarawak have been recruited in this investigation. The study has utilized the mixed-method design, specifically the exploratory sequential design. The analysis conducted has yielded that the spiritual-religious coping strategies (i.e. acceptance towards God’s provision, faith, and religious practices) are important aspects in coping with postflood situations. The application of the spiritual-religious coping strategies will enable those who are at risk of facing flood disaster to be better prepared in terms of managing and minimizing the psychological impacts of the disaster